SEED MYCOFLORA OF Lens culinaris MEDDIK. FROM DIFFERENT STORAGE CONDITIONS AND IN-VITRO INHIBITION USING PLANT EXTRACTS - Chhetri, Roshan; Jha, Sanjay Kumar (Ecoprint: An International Journal of Ecology, 2016)
Nine hundred sixty seeds of lentils (Lens culinaris) from three different storage sources were tested for seed fungi using Potato Dextrose Agar (PDA) and Blotter technique. Thirty five different fungi were isolated, PDA method being better than Blotter technique. Seeds from traditional village storage were found to be more infested with fungi than source local market and source Nepal Agricultural Research Centre (NARC). The fungal infestation on seeds from village storage was 49.37%, source NARC was 44.37% and source local market was 30.31%. Aspergillus flavus, Aspergillus niger, Alternaria alternata, Penicillium chrysogenum and Fusarium oxysporum were the fungi having higher incidence and frequency. Surface disinfection by 2% NaOCl reduced the fungal incidence and frequency. The aqueous extract of three plants viz, Ageratum houstonianum, Eclipta prostrata and Vitex negundo at 25%, 50% and 100% concentration were assessed in-vitro for antifungal activity against Alternaria alternata, Aspergillus niger, Chaetomium funicola and Fusarium oxysporum. Among these fungi, Alternaria alternata was best controlled by Ageratum houstonianum; Aspergillus niger by Eclipta prostrata; Fusarium oxysporum by Vitex negundo and Ageratum houstonianum. The inhibition increased from lower concentration (25%) to higher (100%). ECOPRINT 23: 19-27, 2016